Will the embedded service in supply chains play a role in lowering manufacturer’s carbon emission and maintaining economic growth? - Shi, Chengdong; Chen, Lulu; Yu, Weitong; Zhang, Zhiyao (Frontiers in Environmental Science, 2023)
The carbon cap and trade mechanism (CCTM) is forcing companies to reduce carbon emissions. Due to financial and technical constraints, manufacturers responsible for recycling and remanufacturing begin to seek embedded services from energy service companies (ESCOs), marking the emergence of embedded low-carbon service supply chains. To explore the role of embedded low-carbon service in supply chains in lowering manufacturer’s carbon emissions and maintaining economic growth, a decision model for risk-averse closed-loop supply chain for embedded low-carbon service in uncertain markets is built by using the Stackelberg theory and mean-variance (MV) approach. The paper obtains equilibrium decisions, the manufacturer’s expected utility growth, and total carbon emission reduction. Sensitivity analysis is performed for the main parameters. The results indicate that only when the manufacturer’s risk aversion level and consumers’ low-carbon preference are within the range of 0.35-0.9, can the manufacturer bring in embedded low-carbon service by cooperating with an ESCO through revenue-sharing contracts. When there is a higher carbon price, embedded low-carbon service can further increase the manufacturer’s expected utility, maintain economic growth and reduce carbon emissions. Theoretically, this study combines closed-loop supply chains (CLSCs) and embedded low-carbon services, enriching supply chain theories by integrating factors such as carbon price, risk aversion level, carbon allowance, and consumers’ low-carbon preference. In addition, the findings provide managerial insights for manufacturers, ESCOs, and governments.